Monitoring the health‐related labelling of foods and non‐alcoholic beverages in retail settings. (17th September 2013) - Rayner, M.; Wood, A.; Lawrence, M.; Mhurchu, C. N.; Albert, J.; Barquera, S.; Friel, S.; Hawkes, C.; Kelly, B.; Kumanyika, S.; L'Abbé, M.; Lee, A.; et al.
Summary: Food labelling on food packaging has the potential to have both positive and negative effects on diets. Monitoring different aspects of food labelling would help to identify priority policy options to help people make healthier food choices. A taxonomy of the elements of health‐related food labelling is proposed. A systematic review of studies that assessed the nature and extent of health‐related food labelling has been conducted to identify approaches to monitoring food labelling. A step‐wise approach has been developed for independently assessing the nature and extent of health‐related food labelling in different countries and over time. Procedures for sampling the food supply, and collecting and analysing data are proposed, as well as quantifiable measurement indicators and benchmarks for health‐related food labelling.